Bacteroides gingivalis vesicles bind to and aggregate Actinomyces viscosus. - Ellen, R P (1989)
Isolated Bacteroides gingivalis 2561 vesicles aggregated suspensions of Actinomyces viscosus and Actinomyces naeslundii of all taxonomy clusters. Vesicles bound near A. viscosus cell walls and among its surface fibrils. Tritiated vesicles bound slightly better to saliva-coated hydroxyapatite (SHA) than to SHA coated with A. viscosus; saturation was approached at the concentrations that were tested. Pretreatment of A. viscosus-coated SHA with vesicles impaired the subsequent adherence of B. gingivalis whole cells.